KOMBINASI KACANG MERAH DAN KULIT KACANG HITAM PADA TIKUS WISTAR MODEL DIABETES MELITUS TIPE 2 - Wulandari, Pratiwi; Nuhriawangsa, Adi Magna Patriadi; Susilawati, Tri Nugraha (Poltekkes Kemenkes Bandung, 2024)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease that require pharmacological and non-pharmacological therapies. Comsuming functional foods that are high in antioxidants and fiber such as red beans and black beans beneficial to patients with T2DM. The study aimed to examine the effect of the combination of red beans (Phaseolus vulgaris L.) flour and black beans (Phaseolus vulgaris) coat extract on body weight, blood glucose, insulin level and pancreatic tissue of T2DM model rats. This randomized controlled trial involved 36 male Wistar rats divided into 6 groups consisted of non-diabetic rats (Group I) and nicotinamide-streptozotocin induced diabetic rats (Group II-VI). Group II was negative control; Group III-V were given a combination with the proportion of flavonoid/ fiber in each kgBW as follows: 22.5 mg/0.25 g; 45 mg/0.5 g; and 90 mg/1 g. Group VI was the positive control. Data on body weight, fasting blood glucose levels and insulin levels were analyzed using Two-Way Anova, while pancreatic histopathology scoring data used Kruskal-Wallis.There was a significant difference between the dose and duration of intervention on body weight, fasting blood glucose and insulin levels (p=0.001). The intervention groups showed there were no pancreatic histopathology change as good as the positive control (p>0.05). The combination of flavonoids and fiber at a dose of 45 mg/0.5 g per kgBW was proven to gain weight, reduce fasting blood glucose levels, increase insulin levels and no pancreatic histopathology change in T2DM rats models as well as the postive control group.